Correlations and path analysis for quantitative characteristics in semi-prostrate cowpea bean genotypes (Vigna unguiculata (L.) Walp) - Araméndiz-Tatis, Hermes; Espitia-Camacho, Miguel; Cardona-Ayala, Carlos (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
The cowpea is the most important legume in the Colombian Caribbean, due to its positive impact on the food and nutritional security of low-income rural families. It is cultivated by small producers, but its yields per hectare do not exceed 600 kg, due to the use of obsolete cultivars. The objective of the research was to estimate the correlations between seven quantitative characters and the path analysis between grain yield and six quantitative characters, with the results of the evaluation of 10 genotypes of semi-prostrate growth habit, high grain yield, grown in eight environments of the humid and dry tropics of the Colombian Caribbean region, under the randomized complete blocks design, with four repetitions. Significant differences between environments, genotypes and genotype x environment interaction were detected. Genotypic correlations were of greater magnitude than phenotypic, highlighting the correlation between grain width (GW) and grain yield (GY), rP = 0.69 *, rG = 0.78 *, also between the weight of 100 seeds (100SW) and GW, rP = 0.97 **, rG = 0.99 **. The characters GW and number of pods per plant (NPP) had positive direct effects on the GY, with an indirect negative effect of NPP by way of GW, while the height of the first pod (HFP), the number of seeds per pod (NSP) and the 100SW directly and negatively influenced the GY of the 10 semi-prostrate cowpea cultivars.